Methodological bases of the three-link model criminal proceedings (based on materials of the r epublic of Kazakhstan) (Journal of actual problems of jurisprudence, 2021)
In his address to the people of Kazakhstan “Kazakhstan in the New Reality: Time for Action” dated 1 September 2020, the President of the Republic of Kazakhstan K.-Zh. Tokayev charged all branches of the state power to introduce a three-link model of the criminal process with a clear division of powers, based on maintaining a balance in the system of checks and balances, and creating effective filters at each stage. The implementation of this instruction requires the authorized bodies to solve a set of tasks, which, taken together, should create the right conditions for the effective functioning of the system: “police officer – prosecutor – court”. The experience of the countries of the Organization for Economic Cooperation and Development (OECD) is seen as the basis for such a model. The main advantage of such model, as the President of RK K.-J.K. Tokayev states, is to weaken the prosecution and to prevent illegal interference in criminal proceedings. The purpose of the study is to establish methodological foundations for the introduction of the European model of criminal proceedings in the criminal process of Kazakhstan. The idea of the research: the national model of criminal proceedings should be close to the European model, but not be a copy of it.  Scientific Significance of the work: formulation of scientific prerequisites for legitimate adaptation of the Kazakhstani model of criminal proceedings to the European model. Practical significance: formulation of proposals for amendments and additions to the current Criminal Procedure Code of the RK. Methodology of research: a set of methods of logical-legal analysis of law norms, comparativism, dialectical approach to processes of transformation of legal phenomena into legal phenomena. Value of the conducted research: filling of certain gaps in the methodology of research of problems in the sphere of criminal procedural law. The results of the study has a practical orientation and can be used in the law-making activities related to the improvement of norms of the current Criminal Procedure Code of RK.Keywords: three-link model of criminal procedure, methodology, constitutional law, human rights protection in criminal proceedings.